The Dualism of the Arrangement of Jarimah Khamar and Maisir: A Comparison of Uqubat and Witnesses between Qanun Jinayat Aceh and the Criminal Code in 2023 - Romel Tarigan; Mhd Yadi Harahap (ISNU Sumatera Utara, 2025)
The dualism of the regulation of jarimah khamar and maisir in Indonesia is a consequence of the recognition of legal pluralism in the national legal system. Qanun Jinayat Aceh as a criminal law based on Islamic sharia coexists with the 2023 Criminal Code as a national criminal law. These fundamental philosophical and normative differences cause differences in the formulation of delik, the type of uqubat, as well as the system of proof and witnesses, which has the potential to give rise to legal uncertainty and differences in legal treatment of legal subjects. This study aims to analyze and compare the arrangement of jarimah khamar and maisir between the Qanun Jinayat Aceh and the 2023 Criminal Code, focusing on the difference in uqubat and witness provisions. This study also aims to examine the normative implications of the regulatory dualism in the context of the national criminal law system. The research method used is normative legal research with legislative, conceptual, and comparative legal approaches. Legal materials consist of primary legal materials in the form of related laws and regulations, as well as secondary legal materials in the form of literature, scientific journals, and the doctrine of criminal law and fiqh jinayah. The analysis is carried out qualitatively through systematic and teleological interpretation. The results of the discussion show that Qanun Jinayat Aceh views khamar and maisir as jarimah that threaten the moral and religious order of society, so that uqubat is formulated in the form of ta'zir sanctions that are symbolic and preventive, with a proof system influenced by the principles of fiqh jinayah. The 2023 Criminal Code regulates similar acts within the framework of modern criminal law that focuses on public order and legal certainty, with criminal sanctions of imprisonment and fines as well as a national evidentiary system. This study concludes that the dualism of regulation reflects the challenge of harmonizing national criminal law in a pluralistic legal state, so that legal policies are needed that are able to bridge religious values, legal certainty, and human rights protection proportionately.